Transport and electrical properties of natural rubber/nitrile rubber blend composites reinforced with multiwalled carbon nanotube and modified nano zinc oxide. Issue 5 (5th November 2013) - Thomas, Shaji P.; Thomas, Saliney; Mathew, E.J.; Marykutty, C.V.
<x xml:space="preserve">Abstract</x> As a surface modified zinc oxide, stearic acid‐coated nano zinc oxide (ZOS) has been prepared by sol‐gel method and was used along with N‐benzylimine aminothioformamide‐N‐cyclohexyl benzthiazyl sulfonamide binary accelerator system, multiwalled carbon nanotube (MWCNT) and sulfur for vulcanizing 20/80 natural rubber/nitrile rubber (NR/NBR) blend. Different formulations have been prepared by using 1–7 phr of MWCNT. Solvent transport and electrical properties of the rubber compounds have been investigated. The equilibrium solvent uptake (Q∞) decreased with increase in concentration of the filler due to the decrease in the free volume and the increase in tortuousity. The conductivities of the vulcanizates increased with increase in the dosage of MWCNT from 1 phr in NBCNT1 to 7 phr in NBCNT4 indicating the formation of percolating network of MWCNTs in the NBR/NR matrix. POLYM. COMPOS., 35:956–963, 2014. © 2013 Society of Plastics Engineers